Enhancing the Antioxidant Activity of Technical Lignins by Combining Solvent Fractionation and Ionic‐Liquid Treatment. Issue 21 (24th September 2019) - Majira, Amel; Godon, Blandine; Foulon, Laurence; van der Putten, Jacinta C.; Cézard, Laurent; Thierry, Marina; Pion, Florian; Bado‐Nilles, Anne; Pandard, Pascal; Jayabalan, Thangavelu; Aguié‐Béghin, Véronique; Ducrot, Paul‐Henri; et al.
Abstract: A grass soda technical lignin (PB1000) underwent a process combining solvent fractionation and treatment with an ionic liquid (IL), and a comprehensive investigation of the structural modifications was performed by using high‐performance size‐exclusion chromatography, 31 P NMR spectroscopy, thioacidolysis, and GC–MS. Three fractions with distinct reactivity were recovered from successive ethyl acetate (EA), butanone, and methanol extractions. In parallel, a fraction deprived of EA extractives was obtained. The samples were treated with methyl imidazolium bromide ([HMIM]Br) by using either conventional heating or microwave irradiation. The treatment allowed us to solubilize 28 % of the EA‐insoluble fraction and yielded additional free phenols in all the fractions, as a consequence of depolymerization and demethylation. The gain of the combined process in terms of antioxidant properties was demonstrated through 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH . ) radical‐scavenging tests. Integrating further IL safety‐related data and environmental considerations, this study paves the way for the sustainable production of phenolic oligomers competing with commercial antioxidants. Abstract : Technical lignin refinement : A cascade biorefinery process is presented that enables upgrading of technical lignins and sustainable production of phenolic oligomers of interest as substitutes for commercial antioxidants.